Space, Time, and Architecture - Mikko Heikkinen (Oz, 2007)
The sky is overcast with heavy clouds and snow is falling lightly—perhaps that’s why I’m the only one here. The mounds rise up from the level field, over ten of them in different sizes, some so low that it’s possible to see over them, others two to three meters high.